Mathematical modeling of the melting of ice under conditions of motion of a heat drill; MATEC Web of Conferences; Vol. 194 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2018) - Zakharova E. Ekaterina (Les Ulis, EDP Sciences, 2018)
Title screen